2018
DOI: 10.3390/s18092867
|View full text |Cite
|
Sign up to set email alerts
|

A Sensor Based on a Spherical Parallel Mechanism for the Measurement of Fluid Velocity: Physical Modelling and Computational Analysis

Abstract: In this article, a new method was developed to measure the velocity of a fluid using a sensor, based on the use of a spherical parallel mechanism with three degrees-of-freedom (DOF). This sensor transforms the kinetic energy of the fluid into potential energy by deforming the parallel mechanism. This deformation is due to the impact of the fluid on a sphere attached to the platform of the parallel mechanism. Through the acquisition of data from a sensor using an inertial measurement unit (IMU) in the sphere, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Finally, the velocity of the fluid is calculated by the hydrodynamic Equation of the drag force. The theoretical explanation of this sensor is shown in the paper by the authors of [13] and the demonstration experiment is shown in the paper by the authors of [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the velocity of the fluid is calculated by the hydrodynamic Equation of the drag force. The theoretical explanation of this sensor is shown in the paper by the authors of [13] and the demonstration experiment is shown in the paper by the authors of [14].…”
Section: Methodsmentioning
confidence: 99%
“…For the demonstration of the proposed concepts, a prototype of a planar bipedal robot was developed with a hydraulic actuator and a mechanical sensor that measures the velocity of the fluid relative to the centre of mass of the robot. The theoretical foundation and experimental validation of the sensor are found in [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The forces applied to the sphere due to the movement of the fluid are calculated by equation (6). The calculation has previously been explained in full detail [1].…”
Section: ) Dynamic Forces In the Sphere And Velocitymentioning
confidence: 99%
“…In the article, ''A Sensor Based on a Spherical Parallel Mechanism for the Measurement of Fluid Velocity: Physical Modeling and Computational Analysis'' [1], the researchers proposed a flow sensor [1], [2] that was based on the spherical parallel mechanism with the 2 UPS + 1 RU configuration [3]. They developed a mathematic model and working algorithm for the sensor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation